Evolution of immunoassay with reference to HIV: brief review - Sharma, Rajesh K.; Sharma, Sanjeev K.; Bhushan, Brij; Sharma, Deepa; Kumar, Arun; Chhabra, Reba; Soni, G. R.; Singh, Surinder (International Journal of Medical Research and Review, 2015)
Evolution of rapid test kit and development from first to fourth generation Human Immunodeficiency Virus (HIV) ELISA and CLIA have resulted in high automation, high through put as well as increased sensitivity and specificity. The window period of HIV has decreased whereas blood safety has increased significantly. Despite of all the progress made so far screening test detecting antigen and / or antibodies, although highly effective in identifying infected persons, will not always detect all individuals who are infected and do not correctly classify persons who are not infected. Different generation of ELISA kits have pros & cons and can be used in different algorithm of HIV testing.